Business Information Systems Perspective on the Influence of Work Environment and Workload Toward Career Development and Employee Performance - Sunarmi, Sunarmi; Supriyadi, Andhi; Supriyanto, Sapto (Equator Journal of Management and Entrepreneurship (EJME), 2026)
This research was conducted between December and January 2024 at PT XYZ is a company that provides electrical equipment in the Semarang area and services various types of customers, from large shops to smaller ones around the area. The company's organizational structure consists of 43 team members with various positions, including one director, three managers, seven accountants, twelve marketing staff, nine warehouse staff, and eleven drivers. Data was collected through questionnaires using a Likert scale distributed to employees in various company departments. Data collection aims to obtain their views on the work environment, workload, career development and employee performance. Data analysis uses the path analysis method with the SMART PLS 4 application to test correlation patterns between variables. This research indicates that an employee's career growth is significantly influenced by their work environment. Workload has been shown to have a major impact on professional progress. Additionally, career growth has a major positive impact on worker performance.